Natural Killer Cells Infiltration in the Joints Exacerbates Collagen-Induced Arthritis - Wu, Lisheng; Wang, Ran; Zhou, Yi; Zhao, Di; Chen, Feilong; Wu, Xianghui; Chen, Xiaoguang; Chen, Shixian; Li, Juan; Zhu, Junqing (Frontiers in Immunology, 2022)
Introduction: The role of natural killer (NK) cells in rheumatoid arthritis remains controversial. We aimed to assess the role of NK cells in the pathogenesis of rheumatoid arthritis. Materials and Methods: The percentage of NK cells in the peripheral blood, spleen, lymph nodes and inflamed paws from collagen-induced arthritis mice were examined through the disease progression. Correlation between the proportion of NK cells and subsets with arthritis score, histopathological changes, and bone destruction were evaluated. Adoptive cell transfer was performed to determine the effect of NKp46+NK cells on arthritis development, and the role of receptor NKp46 was explored with NKp46 knockout mice. Results: The percentage of NK cells in peripheral blood decreased at the late stage of the disease and negatively correlated with arthritis score. NK cells increased in the inflamed paws during arthritis development and were positively associated with arthritis score, histopathological change, and bone destruction. Adoptive transfer of NKp46+NK cells before disease onset resulted in increased NK cells infiltration in the joints, higher incidence of arthritis, more severe clinical symptoms, and more pronounced joint inflammation and bone damage. NKp46 deficiency had no significant influence on the incidence and severity of arthritis in collagen-induced arthritis mice. Conclusions: NK cells infiltration in the joints positively correlates with arthritis progression, inflammation, and bone destruction. The pathogenic role of NK cells in rheumatoid arthritis may be independent of the receptor NKp46.